Psychological Factors Affecting Service Behavior of Teachers and Educational Personnel at Early Childhood Care, Development and Education in Thailand - Kantajorn, Supatripa (International Journal of Psychosocial Rehabilitation, 2020)
The purposes of this research are (1) to study the level of service behavior of teachers and educational personnel; (2) to study psychological factors which affected service behavior; and (3) to analyze and check the congruence between the model of psychological factors affecting service behavior and empirical data. The samples consist of 400 teachers and educational personnel who work in the early childhood care. First, the results show that most of teachers and educational personnel are old, seasoned veteran in this field. They have maturity and emotional intelligence along the ages. Their performance are conducted in not only good way, but also regally bound. Second, teachers and educational personnel performing service in the early childhood care have high adversity quotient. The healthy organizational climate causes good working behavior. The organizational climate is the most essential factor affecting working in organization and team working. Moreover, good working behavior arises when the subjective norm occurs. Because the personnel have positive subjective norm and attitudes towards coworkers and supervisors; they realize the advantage and value of the service behavior. They satisfy themselves and serve the children and parent with pleasure. So, they can handle with the problems comprehensively and patiently and conduct good service behavior, good responsibilities for organization and themselves. The parents satisfy the service and come over again.